Assessment of the accuracy of dose calculation in the build-up region of the tangential field of the breast for a radiotherapy treatment planning system - Bagher Farhood; Mohammad Taghi Bahreyni Toossi; Shokouhozaman Soleymanifard; Tohid Mortezazadeh (Contemporary Oncology)
Aim of the study : Our objective was to quantify the accuracy of dose calculation in the build-up region of the tangential field of the breast for a TiGRT treatment planning system (TPS). Material and methods : Thermoluminescent dosimeter (TLD) chips were arranged in a RANDO phantom for the dose measurement. TiGRT TPS was also used for the dose calculation. Finally, confidence limit values were obtained to quantify the accuracy of the dose calculation of the TPS at the build-up region. Results : In the open field, for gantry angles of 15°, 30°, and 60°, the confidence limit values were 17.68, 19.97, and 34.62 at a depth of 5 mm, and 24.01, 19.07, and 15.74 at a depth of 15 mm, respectively. In the wedge field, for gantry angles of 15°, 30°, and 60°, the confidence limit values were 21.64, 26.80, and 34.87 at a depth of 5 mm, and 27.92, 22.04, and 20.03 at a depth of 15 mm, respectively. Additionally, the findings showed that at a depth of 5 mm, the confidence limit values increased with increasing gantry angle while at a depth of 15 mm, the confidence limit values decreased with increasing gantry angle. Conclusions : Overall, TiGRT TPS overestimated doses compared to TLD measurements, and the confidence limit values were greater for the wedge field than for the open fields. Our findings suggest that the assessment of dose distributions in large-dose gradient regions (i.e. build-up region) should not entirely rely on TPS calculations.